Joint bleeds in von Willebrand disease patients have significant impact on quality of life and joint integrity: a cross‐sectional study. (9th April 2015) - van Galen, K. P. M.; Sanders, Y. V.; Vojinovic, U.; Eikenboom, J.; Cnossen, M. H.; Schutgens, R. E. G.; van der Bom, J. G.; Fijnvandraat, K.; Laros‐Van Gorkom, B. A. P.; Meijer, K.; Leebeek, F. W. G.; Mauser‐Bunschoten, E. P.; et al.
<x xml:space="preserve">Abstract</x> Background: Joint bleeds (JB) are reported in a minority of patients with von Willebrand disease (VWD) but may lead to structural joint damage. Prevalence, severity and impact of JB in VWD are largely unknown. Objectives: The aim of this study was to assess JB prevalence, onset, treatment and impact on health‐related quality of life (HR‐QoL) and joint integrity in moderate and severe VWD. Methods: In the Willebrand in the Netherlands study 804 moderate and severe VWD patients [von Willebrand factor (VWF) activity ≤30U dL−1] completed a questionnaire on occurrence, sites and consequences of JB. To analyse JB number, onset, treatment and impact on joint integrity we additionally performed a patient–control study on medical file data comparing patients with JB to age, gender, factor VIII (FVIII)‐ and VWF activity matched VWD patients without JB. Results: Of all VWD patients 23% (184/804) self‐reported JB. These 184 patients reported joint damage more often (54% vs. 18%, P < 0.001) and had lower HR‐QoL (SF36, P < 0.05) compared to VWD patients not reporting JB. Of 55 patients with available JB data, 65% had the first JB before age 16. These 55 patients used more clotting factor concentrate (CFC; median dose 43 vs. 0 IE FVIII kg−1 year−1, P < 0.001), more often had X‐ray joint damage (44% vs. 11%, P = 0.001] and chronic joint pain (44% vs. 18%, P = 0.008) compared to 55 control VWD patients without JB. Conclusion: In conclusion, joint bleeds are reported by 23% of moderate and severe VWD patients, mostly start in childhood, are associated with more CFC use, joint pain, lower HR‐QoL and significantly more radiological and self‐reported joint damage.